Mengevaluasi Mutu Layanan Toko Terhubung dengan Model Pengukuran E-S-Qual - , RIKA PUTRI WAHONO; , Dr. Sahid Susilo Nugroho, MSc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Evaluating the Service Quality on Online Store using E-S-Qual measurement Model In recent year, internet has been choosen by the customer for transaction because the technology of the internet has made it possible to customer to take a greater control to the purchase and consumption experience than ever before. Thatâs why e-commerce is increasing and so many company and online store prefer to offer facility and transact the selling of product and service by online. The purpose of this study are to explore the suitability of E-S-Qual application in particular e-commerce setting on online store store.co.id and to analyze the impacts of website quality upon customer loyalty and actual purchases. There are three regression models on this study. The first model is multiple regression (it measures four dimensions of service quality and perceived value ), the second and the third models are simple regression. The simple regression model measure the relationship between loyalty and actual purchases. This research discovered there is no relationship between system availability and perceived value. It showed the relationship between the dimensions of e-service quality (efficiency, fulfillment, and privacy, except system availability) and perceived value. It also suggested that perceived value influenced loyalty , and loyalty didnât influence actual purchases. For researcher and manager, it is really important to know and analyze that high level of E-SQual has positif influences to customer on online market.